y= e^(cost + lnt) then i tired: y= e^cost - e^lnt lny=lne^cost- lne^lnt (where lne crosses out) lny=cost-lnt 1/y y' =-sint - 1/t y' = e^cost- e^lnt (-sint - 1/t) but the answer is: e^cost (1- tsint)
Follow Math Help Forum on Facebook and Google+
Originally Posted by genlovesmusic09 y= e^(cost + lnt) then i tired: y= e^cost - e^lnt ---------> this is wrong y= e^(cost + lnt) = e^(cos t) * e^(ln t) Do you know what e^(ln t) equals to ? Then you can use the prroduct rule for derivative.
View Tag Cloud